Comparison of tensile properties of xenopericardium from three animal species and finite element analysis for bioprosthetic heart valve tissue. Issue 3 (1st September 2019) - Rassoli, Aisa; Fatouraee, Nasser; Guidoin, Robert; Zhang, Ze
Abstract: Bioprosthetic heart valves still have poor long‐term durability due to calcification and mechanical failure. The function and performance of bioprostheses is known to depend on the collagen architecture and mechanical behavior of the target tissue. So it is necessary to select an appropriate tissue for such prostheses. In this study, porcine, equine, and bovine pericardia were compared histologically and mechanically. The specimens were analyzed under light microscopy. The planar biaxial tests were performed on the tissue samples by applying synchronic loads along the axial (fiber direction) and perpendicular directions. The measured biaxial data were then fitted into both the modified Mooney‐Rivlin model and the anisotropic four parameter Fung‐type model. The modified Mooney‐Rivlin model was applied to the modeling of the bovine, equine, and porcine pericardia using finite element analysis. The equine pericardium illustrated a wavy collagen bundle architecture similar to bovine pericardium, whereas the collagen bundles in the porcine pericardium were thinner and structured. Wavy pericardia may be preferable candidates for transcutaneous aortic valves because they are less likely to be delaminated during crimping. Based on the biaxial tensile test, the specimens indicated some degree of anisotropy; the anisotropy rates of the equine specimens were almost identical, and higher than the other two specimens. In general, porcine pericardium appeared stiffer, based on the greater strain energy magnitude and the average slope of the stress–stretch curves. Moreover, it was less distensible (due to lower areal strain) than the other two pericardial tissues. Furthermore, the porcine model induced localized high stress regions during the systolic and diastolic phases of the cardiac cycle. However, increased mechanical stress on the bioprosthetic leaflets may cause tissue degeneration and reduce the long‐term durability of the valve. Based on our observations, the pericardial specimens behaved as anisotropic and nonlinear tissues—well‐characterized by both the modified Mooney‐Rivlin and the Fung‐type models. The results indicate that, compared to bovine pericardium, equine tissue is mechanically and histologically more appropriate for manufacturing heart valve prostheses. The results of this study can be used in the design and manufacture of bioprosthetic heart valves.